Pelatihan Pembuatan Media Belajar Inovatif pada Kurikulum Merdeka bagi Guru-Guru di Kolbano - Dorthea Maria Woga Nay; Sudirman Sudirman; Yosep Lawa; Heru Christianto; Arvinda C. Lalang; Eka Buang S. Kalla; Eka C. G. Kerihi (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
The training activity for creating innovative learning media in the independent curriculum was carried out in order to develop the competence and skills of teachers related to creating creative and interesting learning media. The activity was carried out in Kolbano, South Central Timor Regency, East Nusa Tenggara Province in 2024. The basis for its implementation was the need for teachers to develop their competence in utilizing technology in creating learning media according to the demands of the current independent curriculum. This activity aims to improve teacher competence in utilizing technology to design interesting and innovative learning. The innovative learning media that were the topic of this training were Google Sites, Wordwall and QuizWhizzer. Teachers in Kolbano generally only teach using lecture and group discussion methods, and use conventional learning media such as power point displays and video materials. As a result, students are less motivated and feel bored in learning activities, while the nature of the independent curriculum demands active interaction of students in learning. Therefore, through this training, teachers are trained and assisted in developing innovative learning media until the product is produced and used in learning. This learning media can be presented interactively and attractively so that it can motivate students to participate in learning. Teachers will also be more creative in innovating to develop media that attracts students' interest in accordance with the nature of the independent curriculum.